Increasing the efficiency of rice production through the introduction of resource-saving technologies on the example of rice systems in Krasnodar Territory - Prihodko Igor (EDP Sciences, 2021)
Rice cultivation is the most resource-intensive production in the Russian agro-industrial sector. Historically, the technology of flooded rice cultivation in thу Krasnodar Territory has remained virtually unchanged for more than 90 years. This is due not only to the biological but also to the technological features of its cultivation. In this connection, the issue of optimizing the production process of rice cultivation is becoming increasingly important every year. Global experience in rice cultivation has determined a further direction of research on optimizing rice cultivation technologies, namely the development of a resource-saving technology for drip irrigation of rice. The pioneering research done by domestic scientists to test drip irrigation of rice in Russia has proved the feasibility and effectiveness of their use. This article proposes a modern resource-saving drip irrigation project for rice, which was tested in OOO “Chernoerkovskoe” in the Slavyanskiy District of the Krasnodar Territory. The authors have proved the efficiency of the proposed rice cultivation technology, resulting in the reduction of irrigation norm, material, labour, energy and technical-technological resources in rice production and crops of rice rotation. The introduction of the new technology has improved not only the biometric indicators of rice, but also the ameliorative condition of soils. Drip irrigation technology makes it possible to cultivate rice outside the rice irrigation systems on land previously used for rain-fed agriculture, which will increase not only the potential area under rice cultivation, but also the geography of rice cultivation in Russia.